Lessons in Stories: Why Narrative Medicine Has a Role in Pediatric Palliative Care Training - Natalie Lanocha (MDPI AG, 2021)
Narrative medicine is introduced and explored as a potential tool for developing competency in medical training, including reduction of burnout, sustaining empathy, and allowing for reflective practice. Developing cultural humility, communication skills, ethics, community building, and advocacy are also reviewed as domains that may be bolstered by training in narrative. Applications specific to pediatric palliative care are suggested, along with avenues for further research.